FAKTOR PREDIKTOR NIAT PENGGUNAAN QRIS : STUDI EMPIRIS PADA GENERASI Y DAN GENERASI Z DI INDONESIA - Dyah Cahyaning Swastihayu (2023)
This research is a quantitative study that aims to see the effect of perceived interactivity, perceived risk, and subjective norms on the level of satisfaction and perceived enjoyment, both of which are seen to influence the interest of Generation Y and Generation Z to use QRIS. This research was conducted on Generation Y and Generation Z in Indonesia who have used QRIS facilities. Hypothesis testing in this study uses Structural Equation Modeling (SEM) with the SmartPLS 4.0 application and a significance level of 5% (0.05). The results obtained for this test are that there is a positive and significant influence between perceived interactivity, perceived risk, and subjective norms on the level of satisfaction and perceived enjoyment. And there is a positive and significant influence on the level of satisfaction and perceived enjoyment on the interest of Generation Y and Generation Z in using the QRIS facility.